Perceived Facilitators and Barriers to Participating in a Combination Income-Generating HIV Risk-Reduction Intervention Among Adolescent Girls and Young Women in Nigeria: A Qualitative Study - Nwaozuru, Ucheoma; Tijani, Wakilat; Gbajabiamila, Titi; Obiezu-Umeh, Chisom; Uzoaru, Florida; Ezechi, Oliver; Musa, Adesola Z.; Curley, Jami; BeLue, Rhonda; Iwelunmor, Juliet (Frontiers in Reproductive Health, 2021)
Background: HIV risk-reduction interventions that include income-generating activities are garnering attention as effective strategies to engage adolescent girls and young women (AGYW) towards HIV risk-reduction. To sustain and promote uptake of these interventions researchers must understand factors that may encourage or present barriers to AGYW participating in these interventions. This study explores AGYW perceived barriers and facilitators to participating in a school-based combination income-generating HIV prevention intervention in Nigeria. Methods: A convenience sample of AGYW who participated in a school-based combination income-generating HIV prevention intervention were recruited for the study. Data generated from the focus group discussions (FGDs)(8 discussion groups comprising of 10-12 participants) were analyzed using inductive thematic analysis. Results: A total of ninety-three participants with a mean age of 15.04 years (S D=0.89) participated in the FGDs. Study participants identified several facilitators and barriers to participating in the intervention. Three main themes that emerged as facilitators were: 1) the involvement of young female facilitators in the delivery of intervention components, 2) the opportunity for social interaction with peers during the intervention period and 3) the support and approval from the school authorities. Two main themes were also identified as barriers: 1) sexual conservatism from society and parents and 2) challenges with sustaining a micro-enterprise. Conclusions: Despite the perceived benefits and interest in participating in the intervention, study participants outlined some challenges that may hinder participation in the intervention components. Addressing barriers such as stigma associated with the discussion of sexual health-related topics coupled with the promotion of facilitating factors such as leveraging context-appropriate intervention delivery modalities is important for enhancing the engagement of AGYW in HIV risk-reduction intervention. Our findings can guide future research and design of combination income-generating HIV prevention intervention for in-school AGYW in low-resource settings like Nigeria.